PROCESS ALGEBRA FOR SIMULATION OF COMPLEX DISCRETE SYSTEMS - Novotarsky, M. A. (Radio Electronics, Computer Science, Control, 2024)
In the paper the process algebra as the tool for the formal description of complex discrete systems is submitted. The structure of sets on which variables and expressions of process algebra are determined is considered. Syntactic structures and semantic rules of performance of the operations allowing to set the formal description for simulations with real working load are described. For definition of adequacy of model it is offered to use the principles of equivalence basing on congruence, strong and weak bisimilarity.